Education Webinar Increaces The Knowledge of The Mask Waste Management During COVID-19 Pandemic - Situmorang, Anggia Gracia Marlina; Farahannisa, Kintan Adelia; Rahmawati, Iqlima; Rossyanti, Lynda (Universitas Airlangga, 2022)
Covid-19 caused many countries to implement new policies to combat its transmission. Among these new policies is the mandatory use of face masks in public spaces, which increased their production, consumption, and mask waste in the environment. Insufficient knowledge and awareness about the proper disposal of used masks, especially medical masks, might lead to environmental pollution due to microplastic particles and widespread contamination of Covid-19, which will affect sanitation and clean water supplies. Thus, providing education regarding proper and responsible masks use and disposal is essential to maintain good health for all and reduce potential environmental hazards amidst the Covid-19 pandemic. To understand the effect of providing education on knowledge regarding the use and management of medical masks,